Experimental and numerical analysis of ceramic fiber geopolymer concrete under blast effect - Dalgic, Aras; Polat, Berivan Yilmazer; Savas, Sedat (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2026)
This study employs both experimental and numerical methods to investigate the blast resistance of ceramic fiber-reinforced geopolymer concrete (CFGC), a cement-free material often referred to as green concrete due to its environmentally friendly nature compared to Portland cement concrete (PCC). Geopolymer concrete specimens, formulated with ground granulated blast furnace slag, silica fume, and varying proportions of ceramic fibers, were subjected to blast tests using 50, 100, 150, 200, and 250 grams of trinitroglycerin (TNG). A standard PCC specimen was utilized as a control. The results demonstrate that the incorporation of 10% ceramic fibers significantly enhances the blast resistance of the geopolymer concrete, reducing crater diameters by up to 20% compared to conventional PCC. Furthermore, the finite element model developed in ANSYS Workbench exhibits a strong correlation with the experimental data, validating the predictive capability of the numerical simulations. Overall, this research highlights the immense potential of CFGC as a sustainable, highly durable alternative for structures exposed to blast loads.
Keywords: Geopolymer concrete; ceramic fiber; blast tests; finite element method; ground granulated blast furnace slag; silica fume